Penerapan Metode Explicit Instruction dengan Tipe Learning Start With A Question dalam Mata Pelajaran Qur’an Hadits Pada Siswa Kelas VII MTs NW Buntaji Tahun Pelajaran 2020/2021 - Suburiah Aan Hikmah (Sekolah Tinggi Agama Islam al-Amin, Gersik, Kediri, Lombok Barat, NTB, 2021)
The purpose of the study was to find out how to apply the explicit instruction method with the type of learning start with a question in the subjects of the Qur'an Hadith in class VII MTs NW Buntaji in the 2020/2021 school year. The research used here is a type of classroom action research. In its original term, classroom action research is called Classroom Action Research and has four stages, namely: Planning (planning), Action (Action), Observation (Observation), and reflection. The data collection techniques are observation, test and documentation.Based on the results of the test (Evaluation) in the first cycle, it shows that there are 9 students who have not achieved individual mastery and 6 students have achieved learning mastery of 15 students, the percentage of learning mastery achieved by students is 40% and the average score is 66.3. Classical completeness has not been achieved as expected > 65%. In cycle II the results of data analysis showed that the average score was 76.3 with student learning completeness of 80%. This shows that student learning mastery has been achieved as targeted in the curriculum, namely the percentage of student learning completeness is at least 65%.